98.7k views
1 vote
1. Given f ( x ) = 2x + 1 and g ( x ) = x2 + 2x – 1 find ( f + g ) ( x ) and ( f + g ) ( 2 )

2 Answers

0 votes

Answer: 25 i think not sure !!

Explanation:

User Bearcat
by
4.8k points
4 votes

Answer: = 12

Explanation:

Step 1. Find ( f + g ) ( x )


Since ( f + g ) ( x ) = f ( x ) + g ( x ) then;


( f + g ) ( x ) = ( 2x + 1 ) + (x^2 + 2x -1 )\\ = 2x + 1 + x^2 + 2x -1\\ = x^2 + 4x

Step 2. Find ( f + g ) ( 2 )

To find the solution for ( f + g ) ( 2 ), evaluate the solution above for 2.


Since ( f + g ) ( x ) = x^2 + 4x then;


( f + g ) ( 2 ) = 2^2 + 4(2)\\ = 4 + 8\\ = 12

User Feedy
by
4.3k points